Crucible assembly for induction furnace and preparation method thereof
By designing a crucible assembly including a sintered layer, a fill layer, a crucible lining and a seal, the problem of crucible cracking and filling layer material entering the metal liquid in the induction furnace is solved, efficient metal smelting is achieved, and yield and safety is improved, and service life is extended.
Patent Information
- Application Number
- CN202210915381.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-07-30
AI Technical Summary
The crucibles in existing induction furnaces are prone to cracking during high-temperature smelting, causing fine or coarse alumina sand in the filling layer to enter the metal liquid, causing surface defects and reduced yield, and may even cause short circuits or burning accidents.
A crucible assembly including a crucible, a sintered layer, a filling layer, a crucible outer lining and a sealing body is designed. Through the combination of a sintered layer and a filling layer, high-temperature metal liquid is blocked from contact with the induction coil, avoiding short circuits and surface defects, and through the design of the crucible outer lining and a sealing body, it extends service life and improves safety.
It effectively avoids crucible cracks and filling layer materials entering the metal liquid, improves the yield and safety of smelted silver or silver alloys, extends the service life of the crucible, and reduces production costs.
Smart Images

Figure CN115388652B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal smelting, and in particular relates to a crucible assembly for an induction furnace and a preparation method thereof. Background Art
[0002] Silver and silver alloys are the most widely used precious metal materials, mainly used as electrical contact materials for precision instruments in the aerospace and electronics industries, as well as precious metal jewelry materials.
[0003] At present, the preparation of silver and silver alloy ingots usually adopts vacuum melting in an induction melting furnace. The crucible for melting is generally an alumina crucible. The material of the filling layer between the alumina crucible and the induction coil is generally alumina coarse sand, fine sand and alumina powder. The filling layer is used to connect the alumina crucible and the induction coil, and fix the alumina crucible in the induction coil. The purpose of selecting alumina fine sand and alumina powder is to fill the gap between the alumina coarse sand to prevent large cavities from forming in the filling layer of only alumina coarse sand during the induction melting vibration process. If the alumina crucible cracks during the melting process and forms large cracks, the high-temperature molten metal flows into the filling layer, contacts the induction coil through the cavities, connects the induction coil to cause a short circuit, and even damages the induction coil. It contacts the cooling water in the induction coil to form a large amount of water vapor, causing serious accidents such as furnace explosion.
[0004] During continuous induction melting of silver and silver alloys, the crucible will crack due to multiple thermal expansion and contraction and vibration. After melting more than 5 furnaces of silver and silver alloy ingots, small cracks will form in the crucible, and fine alumina powder will enter the silver and silver alloy liquid from the filling layer; when there are too many cracks, under the impact of high-temperature melt, small crucible pieces will fall off the crucible, causing serious damage to the crucible, resulting in the phenomenon of "porcelain falling" of the crucible. At this time, fine alumina sand and even coarse alumina sand in the filling layer will enter the silver and silver alloy liquid. When the silver and silver alloy liquid is cast into ingots, fine alumina sand and coarse sand will be mixed in the surface layer of the silver and silver alloy ingot, and alumina powder will be dispersed in the entire silver and silver alloy ingot matrix. In the process of planing ingots to remove the oxide scale of silver and silver alloy ingots, because alumina fine sand and coarse sand are mixed in the surface of the ingot, in order to remove the alumina fine sand, more silver and silver alloy will be planed off, reducing the silver and silver alloy bare ingot yield; after the silver and silver alloy are rolled into strip or sheet finished products, the alumina powder dispersed in the silver and silver alloy matrix is exposed, or white dot-shaped surface defects are formed, or white line-shaped surface defects are formed, resulting in the silver and silver alloy strips and sheets. The surface quality is not up to standard, and the product yield is greatly reduced. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a crucible assembly for an induction furnace and a preparation method thereof in view of the above-mentioned deficiencies in the prior art. The crucible assembly of the present invention, which includes a crucible, a sintering layer, a filling layer, a crucible outer lining and a sealing body, can prevent the high-temperature raw materials from contacting the induction coil during smelting, avoid short circuit or furnace explosion, effectively avoid defects such as white spots and white lines on the surface caused by impurities in the smelting process products, and effectively improve the safety, yield rate and production efficiency of smelting silver or silver alloys.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a crucible assembly for an induction furnace, the induction furnace is used for smelting metals, the induction furnace comprises a furnace body, an induction coil is arranged in the furnace body, the crucible assembly can be arranged in the induction coil, and the crucible assembly is characterized in that the crucible assembly comprises a crucible assembly body and a sealing body arranged on the upper part of the crucible assembly body, the crucible assembly body comprises a cavity for accommodating raw materials, and the top of the cavity is open;
[0007] The crucible assembly body comprises a crucible, a sintering layer, a filling layer and a crucible outer lining, wherein the sintering layer, the filling layer and the crucible outer lining are sequentially arranged outside the crucible from the inside to the outside;
[0008] The raw materials of the sintering layer include coarse alumina sand, fine alumina sand and water glass, and the mass ratio of the coarse alumina sand, fine alumina sand and water glass is (4.5~5.5):(2.5~3.5):(1.5~2.5); the raw materials of the filling layer include coarse alumina sand and fine alumina sand, and the mass of the coarse alumina sand is 2 times to 4 times the mass of the fine alumina sand; the crucible outer lining includes an outer lining filler layer and a fiber cloth layer, and the outer lining filler layer is arranged in the fiber cloth layer, and the raw materials of the outer lining filler layer include coarse alumina sand, fine alumina sand, alumina powder and water glass, and the mass ratio of the coarse alumina sand, fine alumina sand, alumina powder and water glass is (1.5~2.5):(0.5~1.5):(0.5~1.5):(0.5~1.5); the raw materials of the sealing body include metal oxide sand and water glass.
[0009] The above-mentioned crucible assembly for induction furnace is characterized in that the metal includes silver, silver alloy, gold, gold alloy, platinum, platinum alloy, palladium or palladium alloy.
[0010] The above-mentioned crucible assembly for induction furnace is characterized in that the crucible is an alumina crucible, a zirconia crucible or a quartz crucible.
[0011] The above-mentioned crucible assembly for induction furnace is characterized in that the particle size of the coarse alumina sand is 0.3mm~0.6mm; the particle size of the fine alumina sand is 0.1mm~0.3mm; the particle size of the alumina powder is 0.01mm~0.03mm; the material of the fiber cloth layer is asbestos cloth and / or glass fiber cloth.
[0012] The above-mentioned crucible assembly for induction furnace is characterized in that the crucible assembly also includes a glass fiber cloth layer, which is arranged between the sintering layer and the filling layer; the glass fiber cloth layer is a glass fiber cloth layer formed by winding the glass fiber cloth along the outer periphery of the sintering layer, and the number of winding layers is 3 to 5 layers.
[0013] The above-mentioned crucible assembly for induction furnace is characterized in that the thickness of the sintered layer is 5mm~20mm; the thickness of the outer lining filler layer is 30mm~50mm.
[0014] In addition, the present invention also provides a method for preparing the above-mentioned crucible assembly for an induction furnace, characterized in that it comprises:
[0015] Step 1, providing a crucible provided with a sintering layer;
[0016] Step 2, providing a crucible outer lining;
[0017] Step 3, assembling the crucible provided with the sintering layer and the crucible outer lining, and providing a filling layer to obtain a crucible assembly body;
[0018] Step 4: seal the crucible to obtain the crucible assembly.
[0019] The above method is characterized in that the step 1 provides a crucible provided with a sintering layer, which specifically comprises:
[0020] Step 101, mixing alumina coarse sand, alumina fine sand and water glass, stirring to obtain a sintering layer raw material slurry;
[0021] Step 102, evenly apply the sintering layer raw material slurry described in step 101 on the crucible to a preset thickness, wrap it with kraft paper, dry it in the shade for 12 hours to 24 hours, remove the kraft paper, and obtain a crucible coated with the sintering layer raw material;
[0022] Step 103, placing the crucible coated with the sintering layer raw material in step 102 into a box-type resistance furnace, baking at 200°C-400°C for 2h-4h, then sintering at 600°C-900°C for 3h-6h, cooling with the furnace, to obtain a crucible provided with a sintering layer.
[0023] The above method is characterized in that providing the crucible outer lining in step 2 specifically includes:
[0024] Step 201, mixing alumina coarse sand, alumina fine sand, alumina powder and water glass, stirring to obtain a raw material for an outer lining filler layer;
[0025] Step 202, placing a first fiber cloth in a cylindrical shape in the induction coil, so that the first fiber cloth is closely attached to the inner wall of the induction coil, to obtain an induction coil covered with the fiber cloth;
[0026] Step 203, placing the second fiber cloth on the refractory bricks, taking the outer lining filler layer raw material of step 201 and evenly laying it on the second fiber cloth, compacting it, so that the outer lining filler layer raw material covers the second fiber cloth, and obtaining the second fiber cloth with the outer lining filler layer raw material; the second fiber cloth and the first fiber cloth are asbestos cloth or glass fiber cloth; the thickness of the outer lining filler layer raw material after compaction is 30 mm to 50 mm;
[0027] Step 204, vertically placing the induction coil provided with the fiber cloth in step 202 at the center of the second fiber cloth provided with the raw material of the outer lining filler layer, placing a plastic tube in the induction coil provided with the fiber cloth, so that the plastic tube is located at the center of the induction coil provided with the fiber cloth, forming an annular cavity between the plastic tube and the induction coil provided with the fiber cloth, filling the raw material of the outer lining filler layer in step 201 into the annular cavity, compacting, removing the plastic tube, and obtaining a crucible outer lining embryo;
[0028] Step 205, leaving the crucible outer lining embryo body in step 204 to stand until solidified, to obtain a solidified crucible outer lining embryo body;
[0029] Step 206: vertically place the nickel rod in the solidified crucible outer lining embryo body in step 205, place the solidified crucible outer lining embryo body with the nickel rod in an induction furnace, start the induction furnace, and bake for 4 hours to 6 hours to obtain the crucible outer lining.
[0030] The above method is characterized in that in step 3, assembling the crucible provided with a sintered layer and the crucible outer lining, providing a filling layer, and obtaining the crucible assembly body specifically comprises:
[0031] Step 301, placing the crucible provided with a sintered layer in step 1 at the center of the outer lining of the crucible in step 2, forming a chamber between the crucible provided with a sintered layer and the outer lining of the crucible, and filling the chamber with a filling layer raw material, compacting it, to obtain a crucible assembly body;
[0032] The sealing in step 4 to obtain the crucible assembly specifically includes:
[0033] Step 401, mixing metal oxide sand and water glass to obtain a viscous mixture for sealing body;
[0034] Step 402: Lay the sealing body of step 401 on the upper part of the crucible assembly body with the viscous mixture to form a sealing coating layer; the height of the sealing coating layer exceeding the crucible assembly body is 10 mm to 20 mm;
[0035] Step 403, vertically place the nickel rod in the component body after the sealing coating layer is formed in step 402, place the component body with the nickel rod in an induction furnace, start the induction furnace, bake for 4h~6h, remove the nickel rod, and obtain the crucible assembly for the induction furnace.
[0036] Compared with the prior art, the present invention has the following advantages:
[0037] 1. The crucible assembly for an induction furnace of the present invention comprises a crucible, a sintering layer, a filling layer, a crucible outer lining and a sealing body, which can prevent the high-temperature raw materials from contacting the induction coil during smelting to avoid short circuit or furnace explosion, and can effectively avoid defects such as white spots and white lines on the surface caused by impurities in the smelting process products, and can effectively improve the safety, yield rate and production efficiency of smelting silver or silver alloys.
[0038] 2. The crucible assembly for an induction furnace of the present invention includes a crucible outer lining that is detachably arranged outside the filling layer, has a long service life, can be used permanently, and is convenient for easily separating the crucible outer lining and the filling layer after knocking off the sealing body, thereby replacing the crucible with a sintered layer inside, which is beneficial to reducing costs.
[0039] 3. The crucible assembly for the induction furnace of the present invention includes a sintering layer arranged outside the crucible. The raw materials of the sintering layer include alumina coarse sand, alumina fine sand and water glass, which can effectively prevent the crack propagation of the crucible and prevent porcelain from falling off, thereby achieving effective protection of the crucible.
[0040] 4. Preferably, the crucible assembly for an induction furnace of the present invention further comprises a glass fiber cloth layer disposed between the sintering layer and the filling layer, which can further prevent the sand body in the filling layer from entering the smelting high-temperature raw material liquid.
[0041] 5. The crucible assembly for an induction furnace of the present invention comprises a sintering layer raw material consisting of coarse alumina sand, fine alumina sand and water glass, and a filling layer raw material consisting of coarse alumina sand and fine alumina sand. On the basis of forming effective sintering protection and filling protection, the alumina powder in the prior art is further prevented from entering the high-temperature raw material liquid during the smelting process.
[0042] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a schematic structural diagram of the crucible assembly for the induction furnace of Example 1.
[0044] Figure 2 50 μm scale SEM photograph of the silver alloy ribbon obtained before the test.
[0045] Figure 3 This is a 10 μm scale SEM photograph of the silver alloy strip obtained before the experiment.
[0046] Figure 4 This is an EDS photograph of the silver alloy strip obtained before the experiment.
[0047] Figure 5 For the corresponding Figure 4 Energy spectrum analysis diagram.
[0048] Figure 6 This is a SEM photograph of the silver alloy strip obtained after the test. DETAILED DESCRIPTION
[0049] Example 1
[0050] This embodiment provides a crucible assembly for an induction furnace, such as Figure 1 As shown, the induction furnace is used for smelting metals, and the metals include silver, silver alloys, gold, gold alloys, platinum, platinum alloys, palladium or palladium alloys. The induction furnace includes a furnace body, and an induction coil is arranged in the furnace body. The crucible assembly can be arranged in the induction coil. The crucible assembly includes a crucible assembly body and a sealing body 6 arranged on the upper part of the crucible assembly body. The crucible assembly body includes a cavity for accommodating raw materials, and the top of the cavity is open; the crucible assembly body includes a wall body that encloses and forms the cavity, and the sealing body 6 is arranged on the wall body;
[0051] The crucible assembly body comprises a crucible 1, a sintered layer 2, a filling layer 4 and a crucible outer lining 5, wherein the cavity is formed in the crucible 1, and the sintered layer 2, the filling layer 4 and the crucible outer lining 5 are sequentially arranged outside the crucible 1 from the inside to the outside;
[0052] The crucible 1 is an alumina crucible, a zirconia crucible or a quartz crucible;
[0053] The raw materials of the sintered layer 2 include alumina coarse sand, alumina fine sand and water glass, and the mass ratio of the alumina coarse sand, alumina fine sand and water glass is (4.5-5.5):(2.5-3.5):(1.5-2.5), for example, it can be 4.5:2.5:1.5, 5.5:3.5:2.5 or 5:3:2. In this embodiment, the mass ratio of the alumina coarse sand, alumina fine sand and water glass is 5:3:2; the particle size of the alumina coarse sand is 0.3mm-0.6mm, and the particle size of the alumina fine sand is 0.1mm-0.3mm;
[0054] The raw materials of the filling layer 4 include alumina coarse sand and alumina fine sand. The mass of the alumina coarse sand is 2 to 4 times the mass of the alumina fine sand, for example, it can be 2 times, 3 times or 4 times. In this embodiment, the mass of the alumina coarse sand is 3 times the mass of the alumina fine sand.
[0055] The crucible outer lining 5 includes an outer lining filler layer and a fiber cloth layer, the outer lining filler layer is arranged in the fiber cloth layer, the raw materials of the outer lining filler layer include alumina coarse sand, alumina fine sand, alumina powder and water glass, the mass ratio of the alumina coarse sand, alumina fine sand, alumina powder and water glass is (1.5~2.5):(0.5~1.5):(0.5~1.5):(0.5~1.5), for example, it can be 1.5:1.5:0.5:0.5, 2.5:0.5: 1.5: 1.5 or 2:1:1:1, the mass ratio of alumina coarse sand, alumina fine sand, alumina powder and water glass in this embodiment is 2:1:1:1; the particle size of the alumina powder is 0.01mm~0.03mm; the material of the fiber cloth layer is asbestos cloth and / or glass fiber cloth;
[0056] The raw materials of the sealing body 6 include metal oxide sand and water glass. The mass of the metal oxide sand is 3 to 4 times the mass of the water glass. The metal oxide sand is magnesia sand or alumina sand. The particle sizes of the magnesia sand and alumina sand are both 0.01 to 0.3 mm.
[0057] The crucible 1 comprises a cylinder and a bottom arranged at the lower part of the cylinder, and the cylinder and the bottom together form the cavity; the shape of the crucible cylinder is preferably a straight cylinder;
[0058] The crucible assembly for the induction furnace of this embodiment further includes a glass cloth layer 3, which is arranged between the sintering layer 2 and the filling layer 4; the glass cloth layer 3 is formed by winding the glass cloth along the outer periphery of the sintering layer 2, and the number of winding layers is 3 to 5; the temperature resistance of the glass cloth can reach 550 to 1200°C, and the glass cloth is purchased from Caiti or Lanliya;
[0059] In the induction furnace crucible assembly of this embodiment, the thickness of the sintered layer 2 is 5 mm to 20 mm; the thickness of the outer lining filler layer is 30 mm to 50 mm;
[0060] The filling layer 4 consists of a vertical wall filling part and a bottom filling part, the vertical wall filling part corresponds to the tube part of the crucible 1, the thickness of the vertical wall filling part is 2 to 3 times the thickness of the crucible 1 wall, and the thickness of the bottom filling part is 1.5 to 2.5 times the thickness of the crucible 1 wall.
[0061] Example 2
[0062] This embodiment provides a method for preparing the crucible assembly for the induction furnace described in Embodiment 1, comprising:
[0063] Step 1: providing a crucible provided with a sintering layer, specifically comprising:
[0064] Step 101, alumina coarse sand, alumina fine sand and water glass are mixed in a mass ratio of 5:3:2, and stirred to obtain a sintering layer raw material slurry; the stirring is stirring until the system hangs on the alumina stirring rod without falling off;
[0065] Step 102, evenly apply the sintering layer raw material slurry described in step 101 on the crucible 1 to a preset thickness, wrap the sintering layer raw material slurry applied on the crucible 1 with kraft paper to fix it, dry it in the shade for 15 hours, remove the kraft paper, and obtain a crucible coated with the sintering layer raw material; the preset thickness is 10 mm;
[0066] Step 103, placing the crucible coated with the sintering layer raw material in step 102 into a box-type resistance furnace, heating it up with the furnace, first baking it at 300° C. for 3 hours, then sintering it at 800° C. for 4 hours, and cooling it with the furnace to obtain a crucible provided with a sintering layer;
[0067] Step 2: providing a crucible outer lining 5, specifically comprising:
[0068] Step 201, mixing alumina coarse sand, alumina fine sand, alumina powder and water glass in a mass ratio of 2:1:1:1, stirring to obtain a raw material for an outer lining filler layer; the stirring is stirring until the system hangs on the alumina stirring rod without falling off;
[0069] Step 202, placing a first fiber cloth in a cylindrical shape in the induction coil, so that the first fiber cloth is closely attached to the inner wall of the induction coil, to obtain an induction coil covered with fiber cloth; the first fiber cloth is in a rectangular shape, the length of the first fiber cloth is 1.5 times the inner circumference of the induction coil, and the width of the first fiber cloth is the height of the induction coil + 100 mm;
[0070] Step 203, placing the second fiber cloth on the refractory bricks, taking part of the outer lining filler layer raw material of step 201 and evenly laying it on the second fiber cloth, compacting it, so that the outer lining filler layer raw material covers the second fiber cloth, and obtaining the second fiber cloth covered with the outer lining filler layer raw material; the diameter of the second fiber cloth is 1.2 times the diameter of the induction coil; the second fiber cloth and the first fiber cloth are both asbestos cloth; the thickness of the outer lining filler layer raw material after compaction is 40 mm;
[0071] Step 204, vertically placing the induction coil provided with the fiber cloth in step 202 at the center of the second fiber cloth provided with the raw material of the outer lining filler layer, placing the plastic tube in the induction coil provided with the fiber cloth, so that the plastic tube is located at the center of the induction coil provided with the fiber cloth, forming an annular cavity between the plastic tube and the induction coil provided with the fiber cloth, filling part of the raw material of the outer lining filler layer in step 201 into the annular cavity, compacting, removing the plastic tube, and obtaining a crucible outer lining embryo; the diameter of the plastic tube - the crucible diameter ≥ 60 mm;
[0072] Step 205, leaving the crucible outer lining embryo body in step 204 to stand for 36 hours until solidified, to obtain a solidified crucible outer lining embryo body;
[0073] Step 206, vertically placing a nickel rod in the center of the solidified crucible outer lining embryo body in step 205, placing the solidified crucible outer lining embryo body with the nickel rod in an induction furnace, starting the induction furnace, and baking for 5 hours to obtain a crucible outer lining 5; to remove moisture; the furnace temperature is 1000°C;
[0074] Step 3: assembling a crucible provided with a sintered layer and a crucible outer lining 5, and providing a filling layer to obtain a crucible assembly body; specifically comprising:
[0075] Step 301, placing the crucible provided with a sintered layer in step 103 at the center of the crucible outer lining in step 206, forming a chamber between the crucible provided with a sintered layer and the crucible outer lining, loading a filling layer raw material into the chamber, compacting, and obtaining a crucible assembly body; the filling layer raw material is a mixture of alumina coarse sand and alumina fine sand, and the mass of the alumina coarse sand is 3 times the mass of the alumina fine sand; the top of the sintered layer and the top of the crucible outer lining are flush with the crucible opening, and the distance between the filling layer 4 and the crucible opening is 25 mm;
[0076] Step 4: sealing to obtain a crucible assembly, specifically comprising:
[0077] Step 401, mixing metal oxide sand and water glass in a mass ratio of 3:1 to obtain a viscous mixture for a sealing body;
[0078] Step 402: Lay the sealing body of step 401 on the upper part of the crucible assembly body of step 301 with the viscous mixture to form a sealing coating layer; the sealing coating layer exceeds the height of the crucible assembly body by 15 mm, and the sealing coating layer fills the space between the filling layer 4 and the crucible opening; the crucible assembly for the induction furnace of this embodiment can be smelted 45 to 50 times, and when it needs to be replaced, the sealing body is taken out to separate the outer lining of the crucible from the filling layer;
[0079] Step 403, vertically place the nickel rod in the center of the component body after the sealing coating layer is formed in step 402, place the component body with the nickel rod in an induction furnace, start the induction furnace, bake for 5 hours, remove the nickel rod, and obtain a crucible assembly for the induction furnace; to remove moisture; the furnace temperature is 1000°C.
[0080] Example 3
[0081] This embodiment is the same as Embodiment 2, except that step three further includes winding the glass fiber cloth onto the crucible provided with the sintering layer, the number of winding layers being 3 to 5 layers; and tying a knot at the tail to prevent the wound glass fiber cloth from becoming loose.
[0082] Example 4
[0083] This embodiment provides a method for preparing the crucible assembly for the induction furnace described in Embodiment 1, comprising:
[0084] Step 1: providing a crucible provided with a sintering layer, specifically comprising:
[0085] Step 101, alumina coarse sand, alumina fine sand and water glass are mixed in a mass ratio of 5:3:2, and stirred to obtain a sintering layer raw material slurry; the stirring is stirring until the system hangs on the alumina stirring rod without falling off;
[0086] Step 102, evenly apply the sintering layer raw material slurry described in step 101 on the crucible 1 to a preset thickness, wrap the sintering layer raw material slurry applied on the crucible 1 with kraft paper to fix it, dry it in the shade for 12 hours, remove the kraft paper, and obtain a crucible coated with the sintering layer raw material; the preset thickness is 5 mm;
[0087] Step 103, placing the crucible coated with the sintering layer raw material in step 102 into a box-type resistance furnace, heating it up with the furnace, first baking it at 200° C. for 4 hours, then sintering it at 600° C. for 6 hours, and cooling it with the furnace to obtain a crucible provided with a sintering layer;
[0088] Step 2: providing a crucible outer lining 5, specifically comprising:
[0089] Step 201, mixing alumina coarse sand, alumina fine sand, alumina powder and water glass in a mass ratio of 2:1:1:1, stirring to obtain a raw material for an outer lining filler layer; the stirring is stirring until the system hangs on the alumina stirring rod without falling off;
[0090] Step 202, placing a first fiber cloth in a cylindrical shape in the induction coil, so that the first fiber cloth is closely attached to the inner wall of the induction coil, to obtain an induction coil covered with fiber cloth; the first fiber cloth is in a rectangular shape, the length of the first fiber cloth is 1.5 times the inner circumference of the induction coil, and the width of the first fiber cloth is the height of the induction coil + 100 mm;
[0091] Step 203, placing the second fiber cloth on the refractory brick, taking part of the outer lining filler layer raw material of step 201 and evenly laying it on the second fiber cloth, compacting it, so that the outer lining filler layer raw material covers the second fiber cloth, and obtaining the second fiber cloth with the outer lining filler layer raw material; the diameter of the second fiber cloth is 1.2 times the diameter of the induction coil; the second fiber cloth is asbestos cloth, and the second fiber cloth is glass fiber cloth; the thickness of the outer lining filler layer raw material after compaction is 30 mm;
[0092] Step 204, vertically placing the induction coil provided with the fiber cloth in step 202 at the center of the second fiber cloth provided with the raw material of the outer lining filler layer, placing the plastic tube in the induction coil provided with the fiber cloth, so that the plastic tube is located at the center of the induction coil provided with the fiber cloth, forming an annular cavity between the plastic tube and the induction coil provided with the fiber cloth, filling part of the raw material of the outer lining filler layer in step 201 into the annular cavity, compacting, removing the plastic tube, and obtaining a crucible outer lining embryo; the diameter of the plastic tube - the crucible diameter ≥ 60 mm;
[0093] Step 205, leaving the crucible outer lining embryo body in step 204 to stand for 24 hours until solidified, to obtain a solidified crucible outer lining embryo body;
[0094] Step 206, vertically placing a nickel rod in the center of the solidified crucible outer lining embryo body in step 205, placing the solidified crucible outer lining embryo body with the nickel rod in an induction furnace, starting the induction furnace, and baking for 4 hours to obtain a crucible outer lining 5; to remove moisture; the furnace temperature is 800°C;
[0095] Step 3: assembling a crucible provided with a sintered layer and a crucible outer lining 5, and providing a filling layer to obtain a crucible assembly body; specifically comprising:
[0096] Step 301, placing the crucible provided with a sintered layer in step 103 at the center of the crucible outer lining in step 206, forming a chamber between the crucible provided with a sintered layer and the crucible outer lining, loading a filling layer raw material into the chamber, compacting, and obtaining a crucible assembly body; the filling layer raw material is a mixture of alumina coarse sand and alumina fine sand, and the mass of the alumina coarse sand is 3 times the mass of the alumina fine sand; the top of the sintered layer and the top of the crucible outer lining are flush with the crucible opening, and the distance between the filling layer 4 and the crucible opening is 20 mm;
[0097] Step 4: sealing to obtain a crucible assembly, specifically comprising:
[0098] Step 401, mixing metal oxide sand and water glass in a mass ratio of 3:1 to obtain a viscous mixture for a sealing body;
[0099] Step 402: Lay the sealing body of step 401 on the upper part of the crucible assembly body of step 301 with the viscous mixture to form a sealing coating layer; the sealing coating layer exceeds the crucible assembly body by 10 mm, and the sealing coating layer fills the space between the filling layer 4 and the crucible opening;
[0100] Step 403, vertically place the nickel rod in the center of the component body after the sealing coating layer is formed in step 402, place the component body with the nickel rod in an induction furnace, start the induction furnace, bake for 4 hours, remove the nickel rod, and obtain a crucible assembly for the induction furnace; to remove moisture; the furnace temperature is 800°C.
[0101] The performance of the crucible assembly for the induction furnace obtained in this embodiment is basically consistent with that in Example 2.
[0102] Example 5
[0103] This embodiment provides a method for preparing the crucible assembly for the induction furnace described in Embodiment 1, comprising:
[0104] Step 1: providing a crucible provided with a sintering layer, specifically comprising:
[0105] Step 101, alumina coarse sand, alumina fine sand and water glass are mixed in a mass ratio of 5:3:2, and stirred to obtain a sintering layer raw material slurry; the stirring is stirring until the system hangs on the alumina stirring rod without falling off;
[0106] Step 102, evenly apply the sintering layer raw material slurry described in step 101 on the crucible 1 to a preset thickness, wrap the sintering layer raw material slurry applied on the crucible 1 with kraft paper to fix it, dry it in the shade for 24 hours, remove the kraft paper, and obtain a crucible coated with the sintering layer raw material; the preset thickness is 20 mm;
[0107] Step 103, placing the crucible coated with the sintering layer raw material in step 102 into a box-type resistance furnace, heating it up with the furnace, first baking it at 400° C. for 2 hours, then sintering it at 900° C. for 3 hours, and cooling it with the furnace to obtain a crucible provided with a sintering layer;
[0108] Step 2: providing a crucible outer lining 5, specifically comprising:
[0109] Step 201, mixing alumina coarse sand, alumina fine sand, alumina powder and water glass in a mass ratio of 2:1:1:1, stirring to obtain a raw material for an outer lining filler layer; the stirring is stirring until the system hangs on the alumina stirring rod without falling off;
[0110] Step 202, placing a first fiber cloth in a cylindrical shape in the induction coil, so that the first fiber cloth is closely attached to the inner wall of the induction coil, to obtain an induction coil covered with fiber cloth; the first fiber cloth is in a rectangular shape, the length of the first fiber cloth is 1.5 times the inner circumference of the induction coil, and the width of the first fiber cloth is the height of the induction coil + 100 mm;
[0111] Step 203, placing the second fiber cloth on the refractory bricks, taking part of the outer lining filler layer raw material of step 201 and evenly laying it on the second fiber cloth, compacting it, so that the outer lining filler layer raw material covers the second fiber cloth, and obtaining the second fiber cloth covered with the outer lining filler layer raw material; the diameter of the second fiber cloth is 1.2 times the diameter of the induction coil; the second fiber cloth and the first fiber cloth are both glass fiber cloth; the thickness of the outer lining filler layer raw material after compaction is 50 mm;
[0112] Step 204, vertically placing the induction coil provided with the fiber cloth in step 202 at the center of the second fiber cloth provided with the raw material of the outer lining filler layer, placing the plastic tube in the induction coil provided with the fiber cloth, so that the plastic tube is located at the center of the induction coil provided with the fiber cloth, forming an annular cavity between the plastic tube and the induction coil provided with the fiber cloth, filling part of the raw material of the outer lining filler layer in step 201 into the annular cavity, compacting, removing the plastic tube, and obtaining a crucible outer lining embryo; the diameter of the plastic tube - the crucible diameter ≥ 60 mm;
[0113] Step 205, leaving the crucible outer lining embryo body in step 204 to stand for 48 hours until solidified, to obtain a solidified crucible outer lining embryo body;
[0114] Step 206, vertically placing a nickel rod in the center of the solidified crucible outer lining embryo body in step 205, placing the solidified crucible outer lining embryo body with the nickel rod in an induction furnace, starting the induction furnace, and baking for 6 hours to obtain a crucible outer lining 5; to remove moisture; the furnace temperature is 1200°C;
[0115] Step 3: assembling a crucible provided with a sintered layer and a crucible outer lining 5, and providing a filling layer to obtain a crucible assembly body; specifically comprising:
[0116] Step 301, placing the crucible provided with a sintered layer in step 103 at the center of the crucible outer lining in step 206, forming a chamber between the crucible provided with a sintered layer and the crucible outer lining, loading a filling layer raw material into the chamber, compacting, and obtaining a crucible assembly body; the filling layer raw material is a mixture of alumina coarse sand and alumina fine sand, and the mass of the alumina coarse sand is 3 times the mass of the alumina fine sand; the top of the sintered layer and the top of the crucible outer lining are flush with the crucible opening, and the distance between the filling layer 4 and the crucible opening is 30 mm;
[0117] Step 4: sealing to obtain a crucible assembly, specifically comprising:
[0118] Step 401, mixing metal oxide sand and water glass in a mass ratio of 4:1 to obtain a viscous mixture for a sealing body;
[0119] Step 402: Lay the sealing body of step 401 on the upper part of the crucible assembly body of step 301 with the viscous mixture to form a sealing coating layer; the sealing coating layer exceeds the crucible assembly body by 20 mm, and the sealing coating layer fills the space between the filling layer 4 and the crucible opening;
[0120] Step 403, vertically place the nickel rod in the center of the component body after the sealing coating layer is formed in step 402, place the component body with the nickel rod in an induction furnace, start the induction furnace, bake for 6 hours, remove the nickel rod, and obtain a crucible assembly for the induction furnace; to remove moisture; the furnace temperature is 1200°C.
[0121] The performance of the crucible assembly for the induction furnace obtained in this embodiment is basically consistent with that in Example 2.
[0122] The yield rate of silver alloy smelting with the crucible assembly of the induction furnace in Example 2 is shown in Table 1. The smelting process includes: putting the silver alloy material into the crucible, sealing the furnace and evacuating the vacuum, starting heating when the vacuum degree is less than 0.1 Pa, heating power is 10kw, until the silver in the crucible is completely melted, continuing heating for 6-8min refining, closing the valve for heating, filling argon to 0.06 MPa-0.08MPa, increasing the heating power to 25kw, heating time is 2min, can be 1100℃, reducing the power to 10kw, casting with electricity, cooling with the furnace for 15min, and taking out of the furnace.
[0123] The yield rate before the test in Table 1 is the yield rate of the product of the above smelting process performed with a conventional alumina crucible, and the yield rate after the test is the yield rate of the product of the above smelting process performed with a crucible assembly prepared by the method described in Example 2, wherein the conventional alumina crucible is an alumina crucible made of 99% Al2O3, i.e., crucible 1 in step 102 of Example 2. It can be seen from Table 1 that the yield rate of the crucible assembly of the present invention is significantly improved, indicating that the crucible assembly of the present invention can effectively avoid the contamination of the silver alloy material by alumina powder in the conventional crucible.
[0124] Table 1 The yield rate of silver alloy smelting using the crucible assembly of the induction furnace in Example 2
[0125]
[0126] Figure 2 and Figure 3 All of them are SEM photos of the silver alloy strips obtained before the experiment. Figure 2 The picture is under the 50μm scale. Figure 3 This is a picture with a 10μm scale. It can be seen that there are defects such as white lines, white dot lines and intermediate particles on the surface of the silver alloy strip.
[0127] Figure 4 This is the EDS photo of the silver alloy strip obtained before the test. Figure 5 For the corresponding Figure 4 Energy spectrum analysis diagram, combined with Figure 4 , Figure 5 It can be seen that the inclusions in the silver alloy strip are aluminum oxide particles. Figure 2~Figure 5 It can be seen that the generation of white spots and white lines on the surface of the silver alloy strip is one of the main reasons for the low yield. It may be that during the rolling process of the silver alloy, the hard aluminum oxide particles are not easy to deform, which damages the surface of the silver alloy, resulting in poor surface quality of the silver alloy and reduced yield.
[0128] Figure 6 The SEM photo of the silver alloy strip obtained after the test is Figure 6 It can be seen that after the test, there are no white spots or white lines on the surface of the silver alloy, the surface quality is good, and the yield rate is higher, indicating that the crucible assembly of the present invention can effectively avoid the contamination of the metal material by the alumina powder.
[0129] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A crucible assembly for an induction furnace, wherein the induction furnace is used for smelting metals, the induction furnace comprises a furnace body, an induction coil is arranged in the furnace body, and the crucible assembly can be arranged in the induction coil, characterized in that: The crucible assembly comprises a crucible assembly body and a sealing body (6) arranged on the upper part of the crucible assembly body, the crucible assembly body comprises a cavity for accommodating raw materials, and the top of the cavity is open; The crucible assembly body comprises a crucible (1), a sintered layer (2), a filling layer (4) and a crucible outer lining (5), wherein the sintered layer (2), the filling layer (4) and the crucible outer lining (5) are sequentially arranged outside the crucible (1) from the inside to the outside; The raw materials of the sintering layer (2) include alumina coarse sand, alumina fine sand and water glass, and the mass ratio of the alumina coarse sand, alumina fine sand and water glass is (4.5-5.5):(2.5-3.5):(1.5-2.5); the raw materials of the filling layer (4) include alumina coarse sand and alumina fine sand, and the mass of the alumina coarse sand is 2 to 4 times the mass of the alumina fine sand; the crucible outer lining (5) includes an outer lining filling layer and a fiber cloth layer, the outer lining filling layer is arranged in the fiber cloth layer, and the raw materials of the outer lining filling layer include alumina coarse sand, alumina fine sand , alumina powder and water glass, the mass ratio of the alumina coarse sand, alumina fine sand, alumina powder and water glass is (1.5-2.5):(0.5-1.5):(0.5-1.5):(0.5-1.5); the raw materials of the sealing body (6) include metal oxide sand and water glass; the particle size of the alumina coarse sand is 0.3mm-0.6mm; the particle size of the alumina fine sand is 0.1mm-0.3mm; the particle size of the alumina powder is 0.01mm-0.03mm; the material of the fiber cloth layer is asbestos cloth and / or glass fiber cloth.
2. The crucible assembly for an induction furnace according to claim 1, characterized in that: The metal includes silver, silver alloy, gold, gold alloy, platinum, platinum alloy, palladium or palladium alloy.
3. The crucible assembly for an induction furnace according to claim 1, characterized in that: The crucible (1) is an alumina crucible, a zirconia crucible or a quartz crucible.
4. The crucible assembly for an induction furnace according to claim 1, characterized in that: The crucible assembly further comprises a glass fiber cloth layer (3), wherein the glass fiber cloth layer (3) is arranged between the sintering layer (2) and the filling layer (4); the glass fiber cloth layer (3) is formed by winding the glass fiber cloth along the periphery of the sintering layer (2), and the number of winding layers is 3 to 5 layers.
5. The crucible assembly for an induction furnace according to claim 1, characterized in that: The thickness of the sintered layer (2) is 5 mm to 20 mm; the thickness of the outer lining filler layer is 30 mm to 50 mm.
6. A method for preparing a crucible assembly for an induction furnace according to any one of claims 1 to 5, characterized in that: include: Step 1, providing a crucible provided with a sintering layer; Step 2: providing a crucible outer lining (5); Step 3: assembling the crucible provided with the sintered layer and the crucible outer lining (5), and providing a filling layer (4) to obtain a crucible assembly body; Step 4: seal the crucible to obtain the crucible assembly.
7. The method according to claim 6, characterized in that In step 1, a crucible provided with a sintering layer is provided, which specifically includes: Step 101, mixing alumina coarse sand, alumina fine sand and water glass, stirring to obtain a sintering layer raw material slurry; Step 102, evenly apply the sintering layer raw material slurry described in step 101 on the crucible (1) to a preset thickness, wrap it with kraft paper, dry it in the shade for 12 hours to 24 hours, remove the kraft paper, and obtain a crucible coated with the sintering layer raw material; Step 103, placing the crucible coated with the sintering layer raw material in step 102 into a box-type resistance furnace, baking at 200°C to 400°C for 2h to 4h, then sintering at 600°C to 900°C for 3h to 6h, cooling with the furnace, to obtain a crucible provided with a sintering layer.
8. The method according to claim 6, characterized in that Providing the crucible outer lining (5) in step 2 specifically includes: Step 201, mixing alumina coarse sand, alumina fine sand, alumina powder and water glass, stirring to obtain a raw material for an outer lining filler layer; Step 202, placing a first fiber cloth in a cylindrical shape in an induction coil, so that the first fiber cloth is closely attached to the inner wall of the induction coil, to obtain an induction coil covered with the fiber cloth; Step 203, placing the second fiber cloth on the refractory bricks, taking the outer lining filler layer raw material of step 201 and evenly laying it on the second fiber cloth, compacting it, so that the outer lining filler layer raw material covers the second fiber cloth, and obtaining the second fiber cloth with the outer lining filler layer raw material; the second fiber cloth and the first fiber cloth are asbestos cloth or glass fiber cloth; the thickness of the outer lining filler layer raw material after compaction is 30 mm to 50 mm; Step 204, vertically placing the induction coil provided with the fiber cloth in step 202 at the center of the second fiber cloth provided with the raw material of the outer lining filler layer, placing a plastic tube in the induction coil provided with the fiber cloth, so that the plastic tube is located at the center of the induction coil provided with the fiber cloth, forming an annular cavity between the plastic tube and the induction coil provided with the fiber cloth, filling the raw material of the outer lining filler layer in step 201 into the annular cavity, compacting, removing the plastic tube, and obtaining a crucible outer lining embryo; Step 205, leaving the crucible outer lining embryo body in step 204 to stand until solidified, to obtain a solidified crucible outer lining embryo body; Step 206: vertically place the nickel rod in the solidified crucible outer lining body of step 205, place the solidified crucible outer lining body with the nickel rod in an induction furnace, start the induction furnace, and bake for 4 hours to 6 hours to obtain the crucible outer lining (5).
9. The method according to claim 6, characterized in that In step 3, the crucible provided with a sintered layer and the crucible outer lining (5) are assembled, and a filling layer is provided to obtain a crucible assembly body, which specifically includes: Step 301, placing the crucible provided with a sintered layer in step 1 at the center of the outer lining of the crucible in step 2, forming a chamber between the crucible provided with a sintered layer and the outer lining of the crucible, and filling the chamber with a filling layer raw material, compacting it, to obtain a crucible assembly body; The sealing in step 4 to obtain the crucible assembly specifically includes: Step 401, mixing metal oxide sand and water glass to obtain a viscous mixture for sealing body; Step 402: Lay the sealing body of step 401 on the upper part of the crucible assembly body with the viscous mixture to form a sealing coating layer; the height of the sealing coating layer exceeding the crucible assembly body is 10 mm to 20 mm; Step 403, vertically place the nickel rod in the component body after the sealing coating layer is formed in step 402, place the component body with the nickel rod in an induction furnace, start the induction furnace, bake for 4h to 6h, remove the nickel rod, and obtain a crucible assembly for the induction furnace.
Citation Information
Patent Citations
Induction melting furnace and furnace body thereof
CN209043023U
High frequency induction melting furnace
JP1995318256A